2018
DOI: 10.1016/j.jare.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

A review on pregnancy complicated by ovarian epithelial and non-epithelial malignant tumors: Diagnostic and therapeutic perspectives

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 94 publications
0
55
0
Order By: Relevance
“… 4 In patients with advanced-stage epithelial ovarian cancer, termination of the pregnancy should be considered when the diagnosis is made in early pregnancy stages. 6 We found that the abortion rates were significantly higher with ovarian malignancy detection in the first trimester than that in later trimesters. Further analysis showed no significant relationships among tumor size, reproductive history, stage, surgical indications and type.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“… 4 In patients with advanced-stage epithelial ovarian cancer, termination of the pregnancy should be considered when the diagnosis is made in early pregnancy stages. 6 We found that the abortion rates were significantly higher with ovarian malignancy detection in the first trimester than that in later trimesters. Further analysis showed no significant relationships among tumor size, reproductive history, stage, surgical indications and type.…”
Section: Discussionmentioning
confidence: 64%
“…Another review has also stated that fertility-sparing surgery can be offered to patients with stage I epithelial ovarian tumors, germ cell ovarian or sex-cord stromal ovarian tumors. 6 In our study, 16 of 28 patients with ovarian cancers at stage I/II received fertility-sparing operations. Although eight patients with ovarian cancers (stage IA/IC) received conservative treatment, such treatment remains strictly limited because of frequent relapse rates.…”
Section: Discussionmentioning
confidence: 91%
“…Currently, serum CA125 is the most commonly used serum marker for screening ovarian cancer, but its levels can also increase in metastatic ovarian tumours and the first trimester of pregnancy (19). Specifically, CA125 levels are low in maternal serum but high in amniotic fluid in the second and third trimesters (20). Therefore, limited by their low sensitivity and specificity and by the pregnancy itself, serum tumour markers could not be used in an effort to establish the diagnosis of primary malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most recently published review studies regarding the therapeutic perspectives for pregnant women diagnosed with ovarian malignancies was published by Boussios et al and was published in March 2018. [ 19 ] The study identified 193 cases of ovarian cancer diagnosed during pregnancy and published until that moment in the English literature and underlined the utility of an adequate comprehensive staging; in cases with presumed early-stage ovarian cancer, multiple biopsies should be taken to exclude any disseminated lesions. Once the negativity of microscopic disease is confirmed, pregnancy preservation can be taken in consideration.…”
Section: Discussionmentioning
confidence: 99%